Optimization of Trajectory Tracking Control in Task Space for Dual-arm Space Robot - Shuo Li; Xixing Li; Yan Zhao (Jixie chuandong)
For trajectory tracking control of a dual-arm space robot with uncontrolled base position and controlled base attitude in task space， an optimal control method based on state dependent Riccati equation （SDRE） is proposed. Firstly， based on the kinematics equation and fully driven dynamics equation of dual-arm space robot in joint space， the underactuated dynamics equation and the Jacobian relationship between the joint and the end of the manipulator are derived. Then， the SDC （state dependent coefficient） matrix is constructed by increasing the state variables， and the optimal tracking controller is designed based on the SDRE control theory， thus the trajectory tracking of the end grab and the base attitude of the dual-arm space robot is realized under the premise of optimizing the output torque energy. Finally， the Lyapunov method is used to prove the asymptotic stability of the system， and the effectiveness of the designed controller is verified by simulation experiments.